Presenting Macbeth through Play Reproduction - Teguh Imam Subarkah (ENGLISH, 2014)
Using drama to teach English results in real communication involving ideas, emotions, feelings appropriateness and adaptability; in short an opportunity to use language in operation which is absent in a conventional drama class where text analysis is emphasized. Such activities add to the teachers' repertoire of pedagogic strategies giving them a wider option of student learner-centered activities as the prospective teacher of English in Ibn Khaldun University of Bogor to be applied further. Using the reproduction and performance technique, drama becomes one of the appropriate student mastery of CBT.